Mentor – A Trustee for Disadvantaged Youth - Vasechko, Lubova (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The perception of oneself and the surrounding environment are developed during childhood. The behaviour of others directly influences the attitude towards oneself and decisions and observations about one`s value. One of the biggest deficiencies of institutional out-of-family care that significantly hinders the comprehensive development of children is the inability of children to form close bonds with adults. To come to a conclusion that you are not loved and worthless means the feel of deep disappointment. The child becomes shore that he has been deceived and abandoned. These thoughts evoke protests, depression, and insecurity. Due to these misconceptions the socioemotional development of children is hindered. The main goal of the mentor programme is to provide an emotional support and promote the well-being of the young people not having felt a real family environment and care. Youth mentoring in Latvia is a comparatively new concept, and there are only few non-governmental organisations providing this kind of support for young people in the high-risk group. It should be mentioned that there has not been a theoretical study about mentoring so far.